Liability in Autonomous Vehicle Accidents: Crafting New Legal Norms for a Driverless Future in Indonesia - Kemmala Dewi; Zain Nizam; Rashid Rahman (Rechtsnormen: Journal of Law, 2025)
Background. The emergence of autonomous vehicles (AVs) presents a transformative challenge to traditional legal systems that were constructed around human-driven transportation. In Indonesia, where the regulatory framework for vehicle liability remains rooted in fault-based principles, the advent of driverless technology demands a fundamental rethinking of accountability, risk distribution, and consumer protection. Purpose. This study aims to examine the legal implications of AV accidents and propose a model for liability allocation that aligns with Indonesia’s socio-legal context and evolving technological landscape.   Method. Using a qualitative normative legal research method, the study analyzes statutory frameworks, comparative legal systems, and case precedents from jurisdictions that have begun regulating autonomous mobility. Results. The findings indicate that existing Indonesian traffic and consumer laws inadequately address the complexities of autonomous decision-making and manufacturer responsibility. A hybrid liability framework combining strict product liability with adaptive insurance mechanisms is proposed to balance technological innovation with public safety. Conclusion. The research concludes that establishing comprehensive legislation on AV accountability is essential for fostering legal certainty, ethical responsibility, and technological trust. These legal norms must evolve in tandem with technological progress to ensure justice in a driverless future.